Ex Vivo Expanded Donor Alloreactive Regulatory T Cells Lose Immunoregulatory, Proliferation, and Antiapoptotic Markers After Infusion Into ATG-lymphodepleted, Nonhuman Primate Heart Allograft Recipients. Issue 9 (19th August 2021) - Ezzelarab, Mohamed B.; Zhang, Hong; Sasaki, Kazuki; Lu, Lien; Zahorchak, Alan F.; van der Windt, Dirk J.; Dai, Helong; Perez-Gutierrez, Angelica; Bhama, Jay K.; Thomson, Angus W.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Regulatory T cell (Treg) therapy is a promising approach to amelioration of allograft rejection and promotion of organ transplant tolerance. However, the fate of infused Treg, and how this relates to their therapeutic efficacy using different immunosuppressive regimens is poorly understood. Our aim was to analyze the tissue distribution, persistence, replicative activity and phenotypic stability of autologous, donor antigen alloreactive Treg (darTreg) in anti-thymocyte globulin (ATG)-lymphodepleted, heart-allografted cynomolgus monkeys. Methods: darTreg were expanded ex vivo from flow-sorted, circulating Treg using activated donor B cells and infused posttransplant into recipients of major histocompatibility complex-mismatched heart allografts. Fluorochrome-labeled darTreg were identified and characterized in peripheral blood, lymphoid, and nonlymphoid tissues and the graft by flow cytometric analysis. Results: darTreg selectively suppressed autologous T cell responses to donor antigens in vitro. However, following their adoptive transfer after transplantation, graft survival was not prolonged. Early (within 2 wk posttransplant; under ATG, tacrolimus, and anti-IL-6R) or delayed (6–8 wk posttransplant; under rapamycin) darTreg infusion resulted in a rapid decline in transferred darTreg in peripheral blood. Following their early or delayed infusion, labeled cells were evident in lymphoid and nonlymphoid organs and the graft at low percentages (<4% CD4 + T cells). Notably, infused darTreg showed reduced expression of immunoregulatory molecules (Foxp3 and CTLA4), Helios, the proliferative marker Ki67 and antiapoptotic Bcl2, compared with preinfusion darTreg and endogenous CD4 + CD25 hi Treg. Conclusions: Lack of therapeutic efficacy of infused darTreg in lymphodepleted heart graft recipients appears to reflect loss of a regulatory signature and proliferative and survival capacity shortly after infusion.